Perceived Job Insecurity and Anxiety. A Multilevel Analysis on Male and Female Workers in European Countries - Bracci, Anna; Riva, Egidio (Frontiers in Sociology, 2020)
A growing body of evidence has been produced on the adverse effects of job insecurity on health and well-being. Current research in the field conveys a few concerns, some of which are related to gender and cross-national differences in the experience of job insecurity. In order to fill these gaps this study draws on three waves (2005, 2010, 2015) of the European Working Conditions Survey and investigates, using mixed-effects logistic regression: i) the relationship between anxiety and perceived job insecurity; and whether such relationship: ii) is different for men and women; iii) and varies across European countries. Results indicate that male and female workers perceiving the risk of involuntary job loss have similar odds of reporting anxiety. Furthermore, the variance in slopes across countries, relative to the general trend, is significant but modest, too, thus suggesting that the relationship under investigation is fairly similar across European countries. Implications of the findings for future research and practice are discussed.